Komplementärmedizin im Krankenhaus Strategien, Konzepte, Umsetzung - Hoefert, Hans-Wolfgang; Michalsen, Andreas; Uehleke, Bernhard (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2014)
The demand for complementary medicine and naturopathy is increasing continuously, regardless of the not always available evidence of the methods. With the exception of special clinics, complementary medicine and naturopathic approaches are rarely offered in hospitals. It is not only in the course of the increasing competition that hospitals in many places are faced with the decision to follow the trend and to complement their own range of indications and treatments with complementary medical offerings. However, there are no criteria and recommendations that can be used as the basis for such essential strategic decisions. This book closes this gap, which supports hospital managers in decision-making as to whether complementary methods and offers should also be established in-house in order to make the facility more attractive to the competition and more economical for the future. The reader receives medical and economic criteria to rationally advance the decision, planning and establishment of new offers in the hospital or in the clinic group. For this purpose, the work shows concrete instructions for action and case examples for the implementation of complementary medicine procedures or areas in the hospital organization.